Perbandingan Fatwa Perkahwinan Beza Agama Antara Muzakarah Majlis Kebangsaan Bagi Hal Ehwal Agama Islam Malaysia Dengan Majlis Ulama Indonesia Dari Perspektif Maqasid Shari’ah: (Comparison of Interfaith Marriage Fatwas Between the National Council for Islamic Religious Affairs Malaysia and the Indonesian Council of Ulema from the Perspective of Maqasid Shariah) - Hakim, Abdul; Ahmad, Ridzwan; Syed Jaafar, Syed Mohd Jeffri (Online Journal of Research in Islamic Studies, 2023)
Interfaith marriage is not a new issue among Muslims. Yet, it has not been fully addressed due to differences in scholarly views. As a result of intermingling of Muslims with non-Muslims, interfaith marriages are difficult to avoid, which if not controlled, may lead to such marriages taking place against the true teachings of Islam. This study was a comparative study of the following three contexts: the background of interfaith marriages in Malaysia and Indonesia; haram and conditional fatwas between the fatwas of the National Council for Islamic Affairs of Malaysia and the Indonesian Ulema Council from the perspective of maqasid shariah and finally, the influence of both fatwas on the practice of interfaith marriages in Malaysia and Indonesia. Data collection was done through documentation and comparative methods, while data analysis was through descriptive qualitative methods using maqasid shariah as the main yardstick. The results of this study showed that fatwa of the Indonesian Ulema Council is more in conformity with maqasid al-shariah from the point of view of preserving religion and lineage compared to the fatwa of the National Council of Malaysia, which allows conditional interfaith marriages, as in the kitabiah descendants of Prophet Yaqub AS. Hence, from the implementation outlook, the fatwa of the National Council of Malaysia is more effective. The acts and laws regulating interfaith marriages in Malaysia are based on specific legal provisions while there are no rulings from the Indonesian Ulema Council. It is hoped that with the fatwa on interfaith marriage, lineage and Islam under al-kulliyyat al-khams for generations of Muslims in Malaysia and Indonesia, will be preserved and the strength of Muslims in various fields will be revitalised.